2014
DOI: 10.1016/j.neuroimage.2014.05.057
|View full text |Cite
|
Sign up to set email alerts
|

Intensive cognitive training in schizophrenia enhances working memory and associated prefrontal cortical efficiency in a manner that drives long-term functional gains

Abstract: We investigated whether intensive computerized cognitive training in schizophrenia could improve working memory performance and increase signal efficiency of associated middle frontal gyri (MFG) circuits in a functionally meaningful manner. Thirty schizophrenia participants and 13 healthy comparison participants underwent fMRI scanning during a letter N-back working memory task. Schizophrenia participants were then randomly assigned to either 80 hours (16 weeks) of cognitive training or a computer games contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
117
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(126 citation statements)
references
References 44 publications
(57 reference statements)
7
117
0
2
Order By: Relevance
“…In addition, CRT has been associated with improvements in other aspects of community functioning, including social adjustment and psychosocial functioning (Harvey and Bowie, 2012b;Medalia and Saperstein, 2013;Wykes et al, 2011). Our findings are also consistent with two recent studies that found enhanced working memory following cognitive training was associated with better occupational functioning (Subramaniam et al, 2014) and that verbal working memory was the strongest predictor of employment status (Kaneda et al, 2009). Overall, the CRT literature suggests that working memory is a viable treatment target and critical for community functioning.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, CRT has been associated with improvements in other aspects of community functioning, including social adjustment and psychosocial functioning (Harvey and Bowie, 2012b;Medalia and Saperstein, 2013;Wykes et al, 2011). Our findings are also consistent with two recent studies that found enhanced working memory following cognitive training was associated with better occupational functioning (Subramaniam et al, 2014) and that verbal working memory was the strongest predictor of employment status (Kaneda et al, 2009). Overall, the CRT literature suggests that working memory is a viable treatment target and critical for community functioning.…”
Section: Discussionsupporting
confidence: 88%
“…Three of these used N-back tasks to assess WM (64-66), one used an N-back task and a lexical task together (67), and another used a verbal memory task (68). …”
Section: Resultsmentioning
confidence: 99%
“…These characteristics promote motivation and elicit neuromodulators, such as dopamine and acetylcholine, which enhance the molecular basis of learning (e.g., synaptic plasticity) [21,22]. Cognitive training programs that incorporate these principles produce neural changes that are associated with behavioral improvements in cognition (including social cognition) and day-to-day functioning for healthy individuals [17,18], people with schizophrenia [19,**23], and people at risk for schizophrenia [**24]. …”
Section: What Is a “Neuroplasticity-based Approach” And How Does It Dmentioning
confidence: 99%
“…These include regions primarily involved in emotion processing – amygdala, somatosensory-related cortex (SRC), ventral striatum, and medial orbitofrontal cortex (MOFC); cognitive control (used in self-regulatory processes) – lateral prefrontal cortex (LPFC), anterior cingulate cortex (ACC), and superior parietal lobe; and theory of mind – superior temporal sulcus (STS), temporoparietal junction (TPJ), posterior cingulate, and medial prefrontal cortex (MPFC) [9]; 2) Schizophrenia is associated with neural dysfunction in these regions, and the degree of dysfunction is related to social cognitive performance and real-world social behavior [*10,11]; and 3) Cognitive deficits related to neural dysfunction in schizophrenia can be improved through behavioral interventions, such as computer-based cognitive training, that promote neuroplasticity. More specifically, intense behavioral practice of a cognitive skill (e.g., working-memory), improves the underlying neural system supporting that skill, and learning-induced neural changes are related to better cognitive performance [**12,1319]. These data indicate that neuroplasticity-based approaches could improve social impairment in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%